Penanaman Nilai Spiritual-Tasawuf pada Peserta Didik Melalui Syair Perahu Karya Syekh Hamzah Fansuri - Arifa, Nur; Mazaya, Nur Widad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Instilling spiritual values ​​in students is an important component in the Islamic education system. Not only in Islamic education-based schools, spiritual values ​​are also important to be instilled by PAI teachers in general-based schools. This is important to do in order to make students good human beings and have good morals. The concept of Sufism itself is one of the spiritual values ​​that can be taught material in the learning process. One of the leading figures of Sufism scholars in Indonesia who teaches Sufism with its own uniqueness in conveying the concept of Sufism, namely using literature, is Syekh Hamzah Fansuri. This is something interesting to discuss and research. This article will discuss how to instill spiritual values ​​in students through the boat poem written by Syekh Hamzah Fansuri. From this research produced 6 spiritual values-tasawwuf taken from 6 stanzas of the boat poem written by Hamzah Fansuri. Keyword: Hamzah Fansuri, Boat Poetry, students